DEVELOPMENT OF ANDROID-BASED VILLAGE INFORMATION SYSTEM APPLICATION IN LOKA VILLAGE, JENEPONTO DISTRICT - Muh Hendri; Imran, Al; Sa’ban Miru, Alimuddin; Yantahin, Muliaty (Jurusan Pendidikan Teknik Elektro, 2025)
The purpose of this study is to develop an Android-based Village information system in Loka Village, Jeneponto Regency and to determine the results of testing the Android-based Village information system in Loka Village, Jeneponto Regency based on the ISO 25010 software standard.This study uses the Research and Development (R&D) type of research and the waterfall development model. Data collection techniques using interviews, documentation and questionnaires. This system was tested using ISO 25010 software quality standards that focus on four aspects, namely functional suitability, portability, usability, and performance efficiency. Functional suitability testing was carried out by two expert lecturers by filling out a questionnaire containing 13 questions regarding the functions designed in the system being developed, it was found thatthis application was feasible to use and worthy of being accepted. Portability testing was carried out by observing the output results produced using Android smartphones in various versions, the results obtained showed that this village information system application ran well on several versions of Android. The results of the usability aspect test used a questionnaire given to 13 respondents with 15 questions and obtained a percentage value of 90.12% with a very feasible category. Performance efficiency testing was carried out using APPTIM by measuring real-time data for the CPU used, which was 137%, 233 Mb memory when the application was used. The results of the study show that the Android-based village information system application developed in Loka Village, Jeneponto Regency, has met the characteristics of ISO 25010 quality standards. This application canbe used by village officials and the Loka Village community to support the management of village information and services more efficiently andeffectively.